Effects of statins on serum sCD40, sCD146 and PAPP-An in patients with coronary heart disease: serum sCD40, sCD146 and PAPP-An in patients with coronary heart disease - Li, Huawen; Zhou, Xia; Zhu, Wenyan; Zhang, Jing (Journal of Medical Biochemistry, 2025)
Objective:To analyze the effects of statins on the levels of sCD40, sCD146 and PAPP-An in patients with coronary heart disease (CHD).Methods:126 patients with CHD treated from September 2022 to September 2024 were divided into study group (n = 84) and control group (n = 42). The study group was randomly divided into group A (n = 42) and group B (n = 42). Patients in the control group were routinely treated with vasodilator, furosemide, digitalis and other cardiotonic agents. On the basis of routine treatment, patients in the study group were treated with Atto vastatin calcium tablets in group An and rosuvastatin calcium tablets in group B. both groups were treated with 20mg/, oral administration before bedtime, and the treatment cycle was 3 months. the cardiac function grade, blood lipid level, serum sCD40, sCD146 and PAPP-A levels and adverse reactions after treatment were compared before and after treatment.Results:After treatment, the cardiac function of the three groups was improved as compared with that before treatment. The effect of patients in the group A and B was better than control group. The blood lipid levels of the three groups were improved after treatment. The blood lipid level of the group A and B was better than control group. The levels of serum sCD40, sCD146 and PAPP-A between group A and group B were no difference, after treatment, these in group A and B were better than control group. After treatment, there were some adverse reactions in all the three groups. Conclusion:Statins are effective in the treatment of sCD40, sCD146 and PAPP-An in patients with CHD, can significantly improve the cardiac function and blood lipid levels of patients with CHD, and effectively regulate the levels of sCD40, sCD146 and PAPP-An in patients with coronary heart disease
Keywords: serum sCD40, sCD146 , PAPP-An ,Statins; coronary heart disease; serum factor